The Suburban Gothic in American Popular Culture - Murphy, B. author. aut Link
VI, 236 p.
Keywords: The first sustained examination of the depiction of American suburbia in gothic and horror films, television and literature from 1948 to the present day. Beginning with Shirley Jackson's The Road Through the Wall , Murphy discusses representative texts from each decade, including I Am Legend , Bewitched , Halloween and Desperate Housewives .